PENGARUH KOMITMEN ORGANISASIONAL DAN DISIPLIN KERJA TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI MEDIASI (Studi Di Dinas Pendidikan Kecamatan Kaliwungu Selatan Kabupaten Kendal) - Andika Tunggul Nugroho, 1352020048 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the Influence of Organizational Commitment and Discipline Work To Performance Through Job Satisfaction As the District Education Office Mediation in South Kaliwungu Kendal. In this study population of all civil servants in the Department of Education District of South Kaliwungu Kendal, while the sample used at least 138 people as respondents with total sampling technique. By the criteria of the respondents is a civil servant in the Department of Education District of South Kaliwungu Kendal. Measurements using a Likert scale with seven (7) alternative answers. Test instrument used was the validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Commitment Organizational positive effect on job satisfaction, (ii) Work Discipline positive effect on job satisfaction, (iii) Commitment Organizational positive effect on performance, (iv) disciplines work berpangruh positively to performance, (v) Job Satisfaction slight positive effect on employee performance.Keywords: Organizational Commitment, Work Discipline, Performance, Job Satisfaction